(untitled) (Journal of the Bangladesh Agricultural University, 2016)
The study was conducted to assess the food security status of pond fish farming under NGO supported and own managed and to evaluate the influential factors of NGOs intervention on pond fish farmers food security in two districts of Bangladesh. Random sampling technique was used to select farmers from two groups of pond fish farming: one is NGO supported and another is own managed farmers. A total of 120 farmers (60 for NGO supported and 60 for own managed) were selected for data collection. To identify the factors influencing the food security status of fish farming households, a food security index (Z) was constructed and food security status of each household was determined based on the food security line using the recommended daily calorie intake approach. Logit model was used to estimate the food security status of households as a function of a set of independent determinants. Based on the recommended daily calorie intake of 2122 kcal, it is observed that 95 percent of the households were food secure and 5 percent households were food insecure in case of NGO supported fish farmers. On the other hand, 30 percent of the households were food secure and 70 percent households were food insecure in case of own managed fish farmers. The result of logit model shows that six out of eight variables included in the model were significant in explaining the variation in food security status. These variables were: age of the household head, education level of the household head, farm size, intervention on fish farming, income from fish and non-farm income. The study, therefore, recommended improved access to technical supports of pond fish farming households is necessary to ensure food security status at the national level. J. Bangladesh Agril. Univ. 13(2): 273-281, December 2015